KEPASTIAN HUKUM TERHADAP SANKSI ADMINISTRASI TERHADAP BEA MASUK ATAS KEGIATAN IMPORTASI DENGAN FASILITAS TARIF PREFERENSI ACFTA (ASEAN – CHINA FREE TRADE AREA) - Fahlafi, Ramadhan Kahfi; Saleh , Moh. (Gapenas Publisher, 2025)
This study aims to analyze legal certainty in the imposition of administrative sanctions for underpayment of import duties in import activities that utilize the ASEAN–China Free Trade Area (ACFTA) preferential tariff facility. The main issues examined include the basis for imposing underpayment and administrative sanctions on imports with preferential tariffs, as well as the legal consequences for importers. This study uses a normative legal research method with a legislative and conceptual approach, through an analysis of the Customs Law and its implementing regulations.The results of the study show that underpayment of import duties in the preferential tariff scheme generally arises due to differences in customs values, errors in the classification of goods (HS Code), or the rejection of preferential facilities due to non-compliance with the rules of origin. In the customs self-assessment system, importers are responsible for the accuracy of customs declarations, so corrections by Customs and Excise officials can result in obligations to pay import duties and taxes, accompanied by administrative sanctions in the form of fines. Normatively, the imposition of these sanctions is valid as long as they meet the principles of legality, legal certainty, and proportionality. Even under a 0% preferential tariff, the provisions of the legislation still allow for the imposition of administrative fines of a certain amount.The legal consequences for importers are not only financial in the form of payment obligations and fines, but also have an administrative impact on their compliance profile, which may affect the level of supervision in the future. However, the legal system provides mechanisms for objection and appeal as a form of legal protection. Thus, legal certainty in the application of administrative sanctions on ACFTA preferential tariff facilities lies in the clarity of norms, transparency of the determination process, and balance between the interests of state revenue and the protection of importers' rights.